Virginal Status and Adolescent Delinquency: The Birds and the Bees, Deviance, and Teens. Issue 12 (2nd December 2017) - Harper, Alexis J.
ABSTRACT: Much of society deems pre-marital adolescent sexual activity to be deviant. Current research seeks to determine if losing one's virginity has an impact on participation in delinquent acts. It is hypothesized that youth who are more socially bonded to conventional people and activities, with higher levels of self-control, will not have participated in sexual intercourse and will have lower rates of delinquency. Data from Add Health are analyzed. Results do not indicate a significant effect of virginal status on delinquency. However, various social bonds were found to differentially effect delinquency for virgins and non-virgins, which may be important to consider.